Orthopedic implant surface treatment method based on femtosecond laser
The microstructure is formed through femtosecond laser treatment and combined with plasma spraying technology, the binding force between the biocoating on the surface of orthopedic implants and the substrate is improved, the problem of insufficient binding force in the prior art is solved, and the service life of the implant is extended.
Patent Information
- Application Number
- CN202510360667.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
In the existing orthopedic implant surface treatment methods, the binding force between the biocoat and the implant matrix is insufficient, which easily leads to coating peeling and implant failure.
Using a femtosecond laser-based surface treatment method, the surface of orthopedic implant substrate is cleaned, dried and femtosecond laser treatment to form a regular arrangement of microstructures, and then plasma sprayed biocoating is performed.
It significantly improves the binding force between the biocoat and orthopedic implant substrate, extends the life of the implant, and is suitable for a variety of orthopedic implant substrates.
Smart Images

Figure CN119870690A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface treatment, and in particular relates to a surface treatment method of an orthopedic implant based on a femtosecond laser. Background Art
[0002] The repair and replacement of large-scale bone defects caused by diseases, trauma and aging has been an important topic that humans have been studying for centuries. However, the clinical treatment of large-scale bone defects is still a global problem. The use of orthopedic implants to reconstruct the structure and function of bone tissue at the defect site is the main treatment method in modern orthopedics.
[0003] The development of orthopedic implants has gone through several stages. The first generation of implants were mainly made of metals, such as titanium alloys and stainless steel. However, the rigidity and weight of these metal materials limited their application range. The second generation of implants used absorbable materials, such as polylactic acid (PLA) and polylactic-co-glycolic acid (PLGA), which can degrade and be gradually replaced by new bone. Recently, the third generation of implants has introduced bioactive materials, such as hydroxyapatite (HA) coatings and growth factor controlled release systems.
[0004] The preparation of biological coatings on the surface of orthopedic implants is a common and very effective method. Biological coatings can promote bone ingrowth or bone growth, so the bonding strength between the coating and the substrate is particularly important. If the bonding strength between the coating and the substrate is insufficient, the peeled-off coating debris may enter the joint movable surface, forming abrasive wear, greatly accelerating the wear of the ball and socket and other dual components, and may also damage the surrounding bones, leading to osteolysis and aseptic loosening, and ultimately causing the implant to fail.
[0005] Plasma spraying biological coating is a preparation method approved by the FDA for clinical use, and has decades of clinical experience. Currently, porous titanium coatings and hydroxyapatite (HA) coatings are widely used in labor, and the substrates are mainly metals such as titanium, titanium alloys, and cobalt, chromium, and molybdenum. At present, the pre-treatment of plasma spraying is mainly sandblasting, which can increase the surface area of the substrate, so that the plasma spray coating forms a mechanical bond with the substrate. For example, CN118109773A discloses a high entropy alloy coating and a preparation method thereof for improving the mechanical properties and biocompatibility of titanium alloys, specifically using ultrasonic cleaning and sandblasting on the titanium alloy substrate, and using atmospheric plasma spraying equipment to deposit the high entropy alloy coating on the treated substrate; CN114099777A discloses a multi-layer active coating for orthopedic implants and a preparation method thereof, which also introduces the active coating by plasma spraying or electrochemical deposition after sandblasting the orthopedic implant.
[0006] However, the physical bond between the substrate and the coating after sandblasting is often weak, which can easily lead to coating peeling. In addition, further cleaning is often required after sandblasting to remove residual sand. If an air gun is used for cleaning, the residual sand is not easy to clean; if acid pickling is used for cleaning, additional chemical pollution is likely to occur. In addition, existing sandblasting can often only be used on metal surfaces (such as titanium and titanium alloys), which greatly limits the application of plasma spraying on orthopedic implant substrates of different materials.
[0007] Therefore, a new surface treatment method for orthopedic implants is still to be developed to improve the bonding force between the orthopedic implant substrate and the biological coating. Summary of the invention
[0008] The purpose of the present invention is to provide a femtosecond laser-based orthopedic implant surface treatment method in order to overcome the defect of the prior art that the biological coating has a weak bonding force with the orthopedic implant matrix.
[0009] The purpose of the present invention can be achieved by the following technical solutions: The present invention first provides a femtosecond laser-based orthopedic implant surface treatment method, the surface treatment method comprising the following steps: S1: Clean and dry the surface of the orthopedic implant substrate; S2: Perform femtosecond laser treatment on the surface of the orthopedic implant substrate to form regularly arranged microstructures on the substrate surface; Wherein, the orthopedic implant substrate includes a metal substrate, a bioceramic substrate and a polymer material substrate; The energy of the femtosecond laser is 40-150 μJ, the wavelength of the femtosecond laser is 1000-1100 nm, and the pulse width of the femtosecond laser is 245-255 fs; The microstructure includes one or more of grooves, lattices or grids; S3: Plasma spraying of biological coating on the surface of the orthopedic implant substrate after femtosecond laser treatment to finally obtain a surface-modified orthopedic implant; Wherein, the biological coating includes a titanium (Ti) coating and a hydroxyapatite (HA) coating.
[0010] Furthermore, the metal substrate includes titanium and titanium alloys, which have good biocompatibility with human bones, can reduce rejection reactions, and have sufficient mechanical strength and corrosion resistance to withstand the challenges of the in vivo environment.
[0011] Furthermore, the bioceramic substrate includes an alumina ceramic substrate and a zirconia ceramic substrate. Alumina and zirconia ceramic materials are usually used to manufacture components such as femoral heads and acetabular cups of artificial joints. The selection of these materials can reduce the wear particles generated on the joint surface, reduce the risk of periprosthetic bone dissolution and prosthesis loosening, and thus extend the service life of the artificial joint.
[0012] Furthermore, the polymer material substrate includes a polyetheretherketone (PEEK) substrate. PEEK has good corrosion resistance, fatigue resistance, self-lubrication, chemical stability and radiolucency, which make PEEK an ideal material for orthopedic implants and can be used in the fields of spinal fusion devices, trauma internal fixation devices, femoral stem prostheses, etc.
[0013] Furthermore, in step S1, the cleaning is performed by ultrasonic cleaning and / or plasma cleaning.
[0014] Furthermore, in step S1, the drying temperature is 50-70°C.
[0015] Furthermore, in step S2, the power of the femtosecond laser is 0.1-20W.
[0016] Furthermore, in step S2, the scanning speed of the femtosecond laser is 0.5-3 m / min.
[0017] Furthermore, in step S2, the spot diameter of the femtosecond laser is 20-50 μm.
[0018] Furthermore, in step S2, the spot spacing of the femtosecond laser is 80-200 μm.
[0019] Furthermore, in step S2, the width of the grooves is 20-80 µm, and the spacing is 80-200 µm.
[0020] Furthermore, in step S2, the hole size of the dot matrix is 20-80µm, and the spacing is 50-100µm.
[0021] Furthermore, in step S2, the width of the grid is 20-80 µm, and the spacing is 80-200 µm.
[0022] Furthermore, in step S2, the surface roughness of the metal substrate and the bioceramic substrate after femtosecond laser treatment is not less than 8 μm.
[0023] Furthermore, in step S2, the surface roughness of the polymer material substrate after femtosecond laser treatment is not less than 20 μm.
[0024] Furthermore, in step S2, the orthopedic implant substrate after femtosecond laser treatment can be cleaned by ultrasonic cleaning, and the cleaning medium includes solvents such as pure water and isopropyl alcohol.
[0025] Furthermore, in step S3, the plasma spraying gun has a power of 40-50 kW, a powder feeding amount of 15-25 g / min, and a spraying distance of 150-250 mm.
[0026] Furthermore, in step S3, when the biological coating is a titanium coating, the plasma spraying is performed in a vacuum environment.
[0027] Furthermore, in step S3, when the biological coating is a hydroxyapatite coating, the plasma spraying is performed in an atmospheric environment.
[0028] Furthermore, in step S3, when the biological coating is a titanium coating, the thickness of the coating is 150-600 µm.
[0029] Furthermore, in step S3, when the biological coating is a hydroxyapatite coating, the thickness of the coating is 20-100 µm.
[0030] Since the thicker the plasma sprayed coating is, the weaker the bonding force is, the thickness of the coating should be controlled within an appropriate range.
[0031] The present invention also provides a surface modified orthopedic implant obtained by the surface treatment method.
[0032] The surface modified orthopedic implant of the invention consists of an orthopedic implant substrate and a biological coating attached to the surface of the orthopedic implant substrate.
[0033] Furthermore, when the biological coating is a titanium coating, the bonding force between the biological coating and the orthopedic implant substrate is not less than 25 MPa.
[0034] Furthermore, when the biological coating is a hydroxyapatite coating, the bonding force between the biological coating and the orthopedic implant substrate is not less than 50 MPa.
[0035] Furthermore, when the biological coating is a hydroxyapatite coating, the crystallinity of hydroxyapatite in the hydroxyapatite coating is 60%-70%.
[0036] Furthermore, the surface modified orthopedic implants include but are not limited to titanium alloy sprayed with HA coating, titanium alloy sprayed with Ti coating, alumina ceramic sprayed with Ti coating, zirconia ceramic sprayed with Ti coating and PEEK sprayed with Ti coating. The specific orthopedic implant substrate and biological coating can be selected according to actual needs.
[0037] The femtosecond laser technology used in the present invention is different from the thermal effect caused by long-wavelength laser-induced molecular vibration. Due to its extremely low pulse width, the femtosecond laser can obtain extremely high peak power with relatively low pulse energy, trigger multi-photon absorption, and achieve the purpose of material removal through ultrafast nonlinear absorption. The thermal effect in the femtosecond laser processing process can be ignored (i.e., cold processing), and spatial selective manipulation of microstructures can be achieved.
[0038] The plasma spraying surface modification process used in the present invention is to feed the powder to be sprayed into the plasma flame so that the powder is melted or semi-melted, and then deposited on the substrate surface at a high speed through the plasma gas to form a coating. The femtosecond laser of the present invention is used as a pre-treatment step for the plasma spraying biological coating to ensure the bonding force of the biological coating after plasma spraying, which is due to the synergistic effect caused by the increase in the surface area of the substrate, the mechanical grip and the change in the physical and chemical properties of the surface.
[0039] During high-speed particle impact, the droplet begins to spread as soon as it hits the substrate, the molten particles begin to expand radially outward, and solidification occurs immediately at the bottom of the droplet, resulting in a deceleration of the liquid motion. The droplet reaches a static state after a finite diffusion time, and due to the high compression experienced by the droplet upon impact, a shock wave is generated and proceeds upward inside the droplet. Therefore, the elastic energy on the compressed liquid is gradually converted into kinetic energy for lateral flow. If the solidification rate and diffusion rate on the planar surface are inconsistent, splashing will occur.
[0040] The adhesion strength is mainly controlled by the contact adhesion area, and a large contact area increases the energy release rate at the interface. The adhesion of plasma sprayed coatings on textured substrates can be affected by the pattern geometry, and the surface contact area of the substrate is changed by laser surface texturing, promoting a larger adhesion area.
[0041] At the same time, by optimizing the femtosecond laser process parameters, the surface wettability of the substrate can be effectively improved, and the surface wettability of the substrate shows super-hydrophilic properties. When the molten particles hit the substrate, the molten particles can be spread out better, spattering can be reduced, and the substrate can be better combined, thus improving the bonding force between the biological coating and the orthopedic implant substrate.
[0042] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses femtosecond laser processing technology to pre-treat common metal substrates, bioceramic substrates or polymer material substrates before plasma spraying of orthopedic implants, which can significantly improve the bonding strength between the plasma sprayed biological coating and the orthopedic implant substrate.
[0043] (2) The femtosecond laser processing technology of the present invention can be applied not only to common metal substrates, but also to the surfaces of bioceramic substrates such as alumina ceramics, zirconia ceramics, and polymer material substrates such as polyetheretherketone. It can obtain a biological coating that meets the bonding strength requirements on the surface of various common orthopedic implant substrates, greatly broadening the application types of orthopedic implant substrates.
[0044] (3) The present invention uses femtosecond laser as a pre-treatment step for plasma spraying biological coatings. Through the synergistic effect caused by the increase in substrate surface area, mechanical grip and changes in surface physical and chemical properties, it ensures that the biological coating after plasma spraying has good bonding strength and will not easily peel off, thereby meeting the bonding strength requirements of orthopedic implants in actual use.
[0045] (4) The present invention can effectively improve the surface wettability of the substrate by optimizing the femtosecond laser process parameters. When the particles in the molten state hit the substrate, the molten particles can be better spread out, splashing can be reduced, and the particles can be better combined with the substrate, thereby improving the bonding force between the biological coating and the orthopedic implant substrate.
[0046] (5) The femtosecond laser of the present invention is a cold processing mode, which does not require subsequent polishing or chemical treatment, and does not generate additional pollution or metal waste during the processing process. It is a very environmentally friendly processing method and can be widely used in the processing of the surface of orthopedic implant substrates.
[0047] (6) The present invention can significantly improve the bonding force between the biological coating and the orthopedic implant substrate through the femtosecond laser process, reduce the wear effect of the peeled-off coating debris on the implant and the bone, and is expected to extend the service life of the orthopedic implant. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The figure is a schematic flow chart of the surface treatment method of orthopedic implants based on femtosecond laser of the present invention.
[0049] Figure 2 This is a schematic diagram of the microstructure of the titanium alloy surface after femtosecond laser treatment in Example 1 of the present invention.
[0050] Figure 3 This is a schematic diagram of the hydrophilicity of the titanium alloy surface after femtosecond laser treatment in Example 1 of the present invention.
[0051] Figure 4 Schematic diagram of the microstructure of the titanium alloy surface after femtosecond laser treatment in Example 2 of the present invention.
[0052] Figure 5 Schematic diagram of the microstructure of the alumina ceramic surface after femtosecond laser treatment in Example 3 of the present invention.
[0053] Figure 6This is a schematic diagram of the microstructure of the zirconia ceramic surface after femtosecond laser treatment in Example 4 of the present invention.
[0054] Figure 7 This is a schematic diagram of the microstructure of the PEEK surface after femtosecond laser treatment in Example 5 of the present invention.
[0055] Figure 8 This is a microscope image of the titanium alloy surface after sandblasting in Comparative Example 1.
[0056] Fig. 9 This is a microscope image of the surface of the alumina ceramic substrate before and after sandblasting in Comparative Example 3.
[0057] Fig.10 Schematic diagram of the peeling of the Ti coating from the surface of the alumina ceramic substrate in Comparative Example 3.
[0058] Fig.11 This is a microscope picture of the surface of the zirconia ceramic substrate before and after sandblasting in Comparative Example 4.
[0059] Fig.12 This is a microscope image of the surface of the PEEK substrate after sandblasting in Comparative Example 5. DETAILED DESCRIPTION
[0060] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0061] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0062] The present invention specifically relates to a femtosecond laser-based orthopedic implant surface treatment method. The surface treatment method is described in detail in Figure 1 , including the following steps: S1: Clean and dry the surface of the orthopedic implant substrate; S2: Perform femtosecond laser treatment on the surface of the orthopedic implant substrate to form regularly arranged microstructures on the substrate surface; S3: Plasma spraying of biological coating on the surface of orthopedic implant substrate after femtosecond laser treatment is performed to finally obtain a surface-modified orthopedic implant.
[0063] The surface-modified orthopedic implants in the following examples are all obtained based on the above-mentioned surface treatment method.
[0064] Example 1
[0065] This embodiment provides a titanium alloy orthopedic implant sprayed with HA coating and a specific surface treatment method thereof, and the specific steps are as follows: (1) The polished titanium alloy substrate was first ultrasonically cleaned with isopropyl alcohol for 10 min, then ultrasonically cleaned with pure water for 10 min, and then placed in a drying oven at 60 °C for drying.
[0066] (2) Femtosecond laser treatment is performed on the surface of the titanium alloy substrate under atmospheric conditions to form a regularly arranged grid microstructure (e.g. Figure 2 as shown).
[0067] In this embodiment, the specific parameters of the femtosecond laser are as follows: energy is 40µJ, spot diameter is 50µm, spot spacing is 200µm, scanning speed is 2.5m / min, wavelength of the femtosecond laser is 1050nm, and pulse width is 250fs.
[0068] In this embodiment, the width of the grooves of the grid microstructure is about 60µm, and the center line distance between the grooves is about 200µm.
[0069] The surface roughness Ra of the titanium alloy before femtosecond laser treatment is 1.231µm, and the surface roughness Ra of the titanium alloy after femtosecond laser treatment is 9.624µm.
[0070] (3) The titanium alloy substrate after femtosecond laser treatment was ultrasonically cleaned in pure water for 10 min and then dried in a drying oven at 60 °C.
[0071] (4) The surface of the titanium alloy substrate treated by femtosecond laser is subjected to atmospheric plasma spraying of HA coating, and the thickness of the HA coating is about 100 µm, thereby finally obtaining a titanium alloy orthopedic implant with a sprayed HA coating after surface modification.
[0072] In this embodiment, the specific parameters of plasma spraying are as follows: the equipment used to prepare the HA coating is an atmospheric plasma spraying equipment, voltage: 60V; plasma spray gun power: 45kw; argon flow rate: 20sccm; helium: 30sccm; powder feeding amount: 15g / min; spraying distance: 200mm. The HA crystallinity of the prepared HA coating is 62.7%, there is no other crystalline phase, and the rest is amorphous phase.
[0073] Water drops are added to the surface of the titanium alloy substrate treated by femtosecond laser in this embodiment. Figure 3 As shown, it can be found that the water droplets spread rapidly, indicating that the wettability of the titanium alloy substrate after femtosecond laser treatment is super-hydrophilic. This embodiment improves the surface wettability of the substrate by optimizing the femtosecond laser process parameters. When the particles in the molten state hit the substrate, the molten particles can be spread better, reducing splashing, and then better combined with the substrate, so as to improve the bonding force between the coating and the substrate.
[0074] Example 2
[0075] This embodiment provides a titanium alloy orthopedic implant sprayed with a Ti coating and a specific surface treatment method thereof, and the steps are as follows: (1) The polished titanium alloy substrate was first ultrasonically cleaned with isopropyl alcohol for 10 min, then ultrasonically cleaned with pure water for 10 min, and then placed in a drying oven at 60 °C for drying.
[0076] (2) Femtosecond laser treatment is performed on the surface of the titanium alloy substrate under atmospheric conditions to form a regularly arranged groove microstructure (e.g. Figure 4 as shown).
[0077] In this embodiment, the specific parameters of the femtosecond laser are as follows: energy is 150µJ, spot diameter is 20µm, spot spacing is 80µm, scanning speed is 2.5m / min, wavelength of the femtosecond laser is 1050nm, and pulse width is 250fs.
[0078] In this embodiment, the width of the groove microstructure is 35µm, and the center line distance between the grooves is 80µm.
[0079] The surface roughness Ra of the titanium alloy before femtosecond laser treatment is 1.342µm, and the surface roughness Ra of the titanium alloy after femtosecond laser treatment is 10.392µm.
[0080] (3) The titanium alloy substrate after femtosecond laser treatment was ultrasonically cleaned in pure water for 10 min and then dried in a drying oven at 60 °C.
[0081] (4) The surface of the titanium alloy substrate treated by femtosecond laser is subjected to atmospheric plasma spraying of a Ti coating with a thickness of 500 µm, thereby finally obtaining a titanium alloy orthopedic implant with a sprayed Ti coating after surface modification.
[0082] In this embodiment, the specific parameters of plasma spraying are as follows: the equipment used to prepare the Ti coating is a vacuum plasma spraying equipment, vacuum degree: the vacuum degree is pumped to 0.06mbar, and then argon is introduced to a vacuum degree of 200mbar; voltage: 60V; plasma spray gun power: 50kw; argon flow rate: 20sccm; powder feeding amount: 20g / min; spraying distance: 200mm. The prepared Ti coating is a pure titanium layer, and the specific composition is titanium.
[0083] Example 3
[0084] This embodiment provides an alumina ceramic orthopedic implant sprayed with a Ti coating and a specific surface treatment method thereof, the steps are as follows: (1) The polished alumina ceramic substrate was first ultrasonically cleaned with isopropyl alcohol for 10 min, then ultrasonically cleaned with pure water for 10 min, and then placed in a drying oven at 60°C for drying.
[0085] (2) Femtosecond laser treatment is performed on the surface of an alumina ceramic substrate under atmospheric conditions to form a regularly arranged grid microstructure (e.g. Figure 5 as shown).
[0086] In this embodiment, the specific parameters of the femtosecond laser are as follows: energy is 100 µJ, spot diameter is 35 µm, spot spacing is 100 µm, and scanning speed is 0.5 m / min.
[0087] In this embodiment, the groove width of the grid microstructure is 60µm, and the center line distance between the grooves is 200µm.
[0088] In this embodiment, the surface roughness Ra of the alumina ceramic substrate before pretreatment is 1.618 μm, and the surface roughness Ra after femtosecond laser treatment is 12.366 μm, and the surface roughness is significantly improved.
[0089] (3) The alumina ceramic substrate treated with femtosecond laser was ultrasonically cleaned in pure water for 10 min and then dried in a drying oven at 60 °C.
[0090] (4) The surface of the alumina ceramic substrate treated by femtosecond laser is vacuum plasma sprayed with a Ti coating, and the thickness of the Ti coating is 500 µm. Finally, an alumina ceramic orthopedic implant with a sprayed Ti coating after surface modification is obtained.
[0091] In this embodiment, the specific parameters of plasma spraying are as follows: the equipment used to prepare the Ti coating is a vacuum plasma spraying equipment, vacuum degree: the vacuum degree is pumped to 0.06mbar, and then argon is introduced to a vacuum degree of 200mbar; voltage: 60V; plasma spray gun power: 50kw; argon flow rate: 20sccm; powder feeding amount: 20g / min; spraying distance: 200mm. The prepared Ti coating is a pure titanium layer, and the specific composition is titanium.
[0092] Example 4
[0093] This embodiment provides a zirconia ceramic orthopedic implant sprayed with a Ti coating and a specific surface treatment method thereof, the steps are as follows: (1) The polished zirconia ceramic substrate was first ultrasonically cleaned with isopropyl alcohol for 10 min, then ultrasonically cleaned with pure water for 10 min, and then placed in a drying oven at 60°C for drying.
[0094] (2) Femtosecond laser treatment is performed on the surface of the zirconia ceramic substrate under atmospheric conditions to form a regularly arranged porous lattice microstructure (such as Figure 6 as shown).
[0095] In this embodiment, the specific parameters of the femtosecond laser are as follows: energy is 140 µJ, spot diameter is 40 µm, spot spacing is 150 µm, and scanning speed is 2 m / min.
[0096] In this embodiment, the hole diameter of the lattice microstructure ranges from 20 to 40 µm, and the spacing between the hole centers is about 80 µm.
[0097] In this embodiment, the surface roughness Ra of the zirconia ceramic substrate before pretreatment is 1.009 μm, and the surface roughness Ra after femtosecond laser treatment is 10.777 μm.
[0098] (3) The zirconia ceramic substrate treated with femtosecond laser was ultrasonically cleaned in pure water for 10 min and then dried in a drying oven at 60°C.
[0099] (4) The surface of the zirconia ceramic substrate treated by femtosecond laser is vacuum plasma sprayed with a Ti coating, and the thickness of the Ti coating is 500 µm, thereby finally obtaining a zirconia ceramic orthopedic implant with a sprayed Ti coating after surface modification.
[0100] In this embodiment, the specific parameters of plasma spraying are as follows: the equipment used to prepare the Ti coating is a vacuum plasma spraying equipment, vacuum degree: the vacuum degree is pumped to 0.06mbar, and then argon is introduced to a vacuum degree of 200mbar; voltage: 60V; plasma spray gun power: 50kw; argon flow rate: 20sccm; powder feeding amount: 20g / min; spraying distance: 200mm. The prepared Ti coating is a pure titanium layer, and the specific composition is titanium.
[0101] Example 5
[0102] This embodiment provides a PEEK orthopedic implant sprayed with a Ti coating and a specific surface treatment method thereof, the steps are as follows: (1) The polished PEEK substrate was first ultrasonically cleaned with isopropyl alcohol for 10 min, then ultrasonically cleaned with pure water for 10 min, and then placed in a drying oven at 60 °C for drying.
[0103] (2) Femtosecond laser treatment is performed on the surface of the PEEK substrate under an argon atmosphere to form a regularly arranged groove microstructure (e.g. Figure 7 as shown).
[0104] In this embodiment, the specific parameters of the femtosecond laser are as follows: energy is 50 µJ, spot diameter is 40 µm, spot spacing is 300 µm, and scanning speed is 2.5 m / min.
[0105] In this embodiment, the width of the groove microstructure is 35µm, and the center line distance between the grooves is 80µm.
[0106] In this embodiment, the surface roughness Ra of the PEEK substrate is 3.684 μm, and the surface roughness Ra after femtosecond laser treatment is 26.395 μm.
[0107] (3) The PEEK substrate after femtosecond laser treatment was ultrasonically cleaned in pure water for 10 min and then dried in a drying oven at 60 °C.
[0108] (4) The surface of the PEEK substrate treated by femtosecond laser is subjected to atmospheric plasma spraying of a Ti coating with a thickness of 500 µm, thereby finally obtaining a PEEK orthopedic implant with a sprayed Ti coating after surface modification.
[0109] In this embodiment, the specific parameters of plasma spraying are as follows: the equipment used to prepare the Ti coating is a vacuum plasma spraying equipment, vacuum degree: the vacuum degree is evacuated to 0.06mbar, and then argon gas is introduced, and the vacuum degree is increased to 200mbar; voltage: 60V; plasma spray gun power: 50kw; argon gas flow rate: 20sccm; powder feeding amount: 20g / min; spraying distance: 200mm.
[0110] Comparative Example 1: This comparative example provides a specific treatment method for sandblasting a titanium alloy substrate before plasma spraying HA coating, and the steps are as follows: (1) The polished titanium alloy substrate was first ultrasonically cleaned with isopropyl alcohol for 10 min, then ultrasonically cleaned with pure water for 10 min, and then placed in a drying oven at 60 °C for drying.
[0111] (2) Use F24 type alumina sand for sand blasting. The sand blasting parameters are as follows: sand blasting pressure is 4 bar; sand blasting distance is 15 cm, and the surface is sand blasted to be uniform. The surface morphology after sand blasting is as follows: Figure 8 shown.
[0112] The roughness Ra of the titanium alloy substrate before sandblasting is 1.213µm, and the surface roughness Ra of the alumina substrate after sandblasting is only 4.512µm, which is much lower than the surface roughness of 10.392µm after femtosecond laser treatment.
[0113] (3) Clean the titanium alloy substrate after sandblasting with a compressed air gun.
[0114] (4) The HA coating is atmospheric plasma sprayed on the surface of the titanium alloy substrate after sandblasting, and the thickness of the HA coating is 100 µm.
[0115] Comparative Example 2: This comparative example provides a specific treatment method for sandblasting a titanium alloy substrate before plasma spraying a Ti coating, and the steps are as follows: (1) The polished titanium alloy substrate was first ultrasonically cleaned with isopropyl alcohol for 10 min, then ultrasonically cleaned with pure water for 10 min, and then placed in a drying oven at 60 °C for drying.
[0116] (2) Use F24 type alumina sand for sand blasting. The sand blasting parameters are as follows: sand blasting pressure is 4 bar; sand blasting distance is 15 cm, and sand blasting is performed until the surface is uniform.
[0117] (3) Clean the titanium alloy substrate after sandblasting with a compressed air gun.
[0118] (4) The Ti coating is atmospheric plasma sprayed on the surface of the titanium alloy substrate after sandblasting, and the thickness of the Ti coating is 500 μm.
[0119] Comparative Example 3: In this comparative example, the alumina ceramic substrate was sandblasted before plasma spraying of the Ti coating.
[0120] The specific parameters of sandblasting are as follows: the sandblasting pressure is 4 bar; the sandblasting distance is 15 cm, and the sandblasting is performed until the surface is uniform. The sand material type is aluminum oxide sand material, and the surface morphology of aluminum oxide after sandblasting is as follows Fig. 9 shown.
[0121] The roughness Ra of the alumina substrate before sandblasting is 1.618µm, and the surface roughness Ra of the alumina after sandblasting is only 2.993µm, which is much lower than the surface roughness of 12.366µm after femtosecond laser treatment.
[0122] In addition, after plasma spraying titanium coating, the titanium coating on the surface of alumina ceramic substrate will be directly peeled off under slight human force (such as Fig.10 As shown in the figure, it shows that the bonding force between the alumina ceramic substrate and the titanium coating is weak after sandblasting and cannot meet the corresponding bonding force standard. Therefore, the surface of the alumina ceramic substrate is not suitable for pretreatment modification by sandblasting.
[0123] Comparative Example 4: In this comparative example, the zirconia ceramic substrate was sandblasted before the plasma spraying of the Ti coating. The sandblasting parameters were as follows: the sandblasting pressure was 4 bar; the sandblasting distance was 15 cm, and the sandblasting was performed until the surface was uniform. The sand material model was zirconia sand material. The surface morphology of the alumina after sandblasting was as follows: Fig.11 shown.
[0124] In this embodiment, the roughness Ra of the zirconia substrate before sandblasting is 1.009 µm, and the surface roughness Ra of the zirconia substrate after sandblasting is 2.210 µm, which is much lower than the surface roughness of 10.777 µm after femtosecond laser treatment.
[0125] Observation under a 100x microscope showed that the surface morphology of the zirconia ceramic substrate did not change much before and after sandblasting, indicating that sandblasting did not have the expected surface modification effect on the zirconia ceramic substrate.
[0126] In addition, after plasma spraying titanium coating, the titanium coating will also peel off directly from the zirconia ceramic substrate with only slight manpower, indicating that the bonding force between the zirconia ceramic substrate and the titanium coating is weak after sandblasting and cannot meet the corresponding bonding force standard. Therefore, the surface of the zirconia ceramic substrate is not suitable for pre-treatment surface modification using sandblasting.
[0127] Comparative Example 5: In this comparative example, the PEEK substrate was sandblasted before plasma spraying of the Ti coating.
[0128] The sandblasting parameters are as follows: the sandblasting pressure is 4 bar; the sandblasting distance is 15 cm, and the sandblasting is performed until the surface is uniform. The sand material type is zirconium oxide sand material, and the surface morphology of the aluminum oxide after sandblasting is as follows Fig.12 shown.
[0129] The roughness Ra of the PEEK substrate before sandblasting is 3.684µm, and the surface roughness Ra of the PEEK substrate after sandblasting is 4.616µm, which is much lower than the surface roughness of 26.395µm after femtosecond laser treatment. Sandblasting does not have the expected surface modification effect on the PEEK substrate.
[0130] The surface roughness Ra of the orthopedic implant substrates of Examples 1-5 treated with femtosecond laser and the orthopedic implant substrates of Comparative Examples 1-5 treated with sandblasting are summarized in Table 1.
[0131] Table 1 Summary of surface roughness of orthopedic implant substrates
[0132] As shown in Table 1, after femtosecond laser treatment, a fine micro-nano structure is formed on the surface of the orthopedic implant substrate, thereby improving the surface roughness of the substrate. However, after sandblasting, the orthopedic implant substrate lacks controllable micromorphological changes, and the surface roughness is not significantly different from that before treatment.
[0133] The increase in surface roughness indicates that the substrate surface has a larger contact area, and sufficient contact area will further increase the energy release rate of the interface. The adhesion of plasma sprayed coatings on textured substrates is affected by the geometry of the pattern. The surface contact area of the substrate is changed by laser surface texturing, which enhances the mechanical bite effect between the bio-coating and the substrate, thereby improving the bonding force between the bio-coating and the orthopedic implant substrate. However, the random impact of sandblasting particles during sandblasting only produces macroscopic roughness and lacks controllable micromorphology, which may lead to limited increase in surface area, resulting in no significant difference in surface roughness after sandblasting and before sandblasting.
[0134] In accordance with the provisions of the present invention, the bonding strength between the substrate and the coating after plasma spraying the biological coating in Examples 1-5 and Comparative Examples 1-5 was further tested. The bonding strength requirements, standards and test methods of the corresponding coatings are shown in Table 2. The test results of the bonding strength between the substrate and the coating are summarized in Table 3.
[0135] Table 2 Bonding requirements of plasma sprayed titanium coating and HA coating
[0136] Table 3 Bonding test results of plasma sprayed titanium coating and HA coating
[0137] The results show that for metal materials such as titanium alloy, the tensile strength of the HA coating after sandblasting is 46.36MPa; and after femtosecond laser treatment of the titanium alloy, the tensile strength of the HA coating can reach 71MPa, which is 53.6% higher than the tensile strength of sandblasting, indicating that the bonding strength between the titanium alloy and the HA coating is significantly improved after femtosecond laser treatment.
[0138] For bioceramic materials such as alumina and zirconia ceramics, sandblasting cannot produce effective morphological changes on the ceramic matrix, and the Ti coating is very easy to peel off after plasma spraying, and the bonding force is weak, so it is impossible to perform bonding test. However, after femtosecond laser treatment, alumina ceramics and zirconia ceramics can be well plasma sprayed on the surface of the substrate to form a biocoating, and the tensile strength of the Ti coating can be as high as 34MPa, far exceeding the relevant standard requirements.
[0139] For medical polymer materials such as PEEK, the tensile strength of the titanium coating formed by plasma spraying after sandblasting is 27.791MPa. After femtosecond laser treatment, the tensile strength of the titanium coating is 28.553MPa, which is slightly improved and can fully meet the corresponding standard requirements.
[0140] In summary, the present invention uses femtosecond laser micro-nano processing technology to perform surface treatment on common orthopedic implants such as titanium alloys, alumina ceramics, zirconia ceramics, PEEK, etc. before plasma spraying of the biological coating. The synergistic mechanism of improving the surface hydrophilic wettability, increasing the surface contact and adhesion area, etc. can significantly improve the bonding force between the biological coating and the orthopedic implant substrate, reduce the wear effect of the peeled-off coating debris on the implant and the bone, and is expected to extend the service life of the orthopedic implant.
[0141] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A femtosecond laser-based orthopedic implant surface treatment method, characterized in that: The surface treatment method comprises the following steps: S1: Clean and dry the surface of the orthopedic implant substrate; S2: Perform femtosecond laser treatment on the surface of the orthopedic implant substrate to form regularly arranged microstructures on the substrate surface; Wherein, the orthopedic implant substrate includes a metal substrate, a bioceramic substrate and a polymer material substrate; The energy of the femtosecond laser is 40-150 μJ, the wavelength of the femtosecond laser is 1000-1100 nm, and the pulse width of the femtosecond laser is 245-255 fs; The microstructure includes one or more of grooves, lattices or grids; S3: Plasma spraying of biological coating on the surface of the orthopedic implant substrate after femtosecond laser treatment to finally obtain a surface-modified orthopedic implant; Wherein, the biological coating includes a titanium coating and a hydroxyapatite coating.
2. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: The metal substrate includes titanium and titanium alloys; The bioceramic substrate includes an alumina ceramic substrate and a zirconia ceramic substrate; The polymer material substrate includes a polyetheretherketone substrate.
3. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: In step S2, the scanning speed of the femtosecond laser is 0.5-3 m / min.
4. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: In step S2, the spot diameter of the femtosecond laser is 20-50 μm, and the spot spacing is 80-200 μm.
5. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: In step S2, the width of the groove is 20-80 μm, and the spacing is 80-200 μm; The hole size of the dot matrix is 20-80µm, and the spacing is 50-100µm; The width of the grid is 20-80µm and the spacing is 80-200µm.
6. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: In step S2, the surface roughness of the metal substrate and the bioceramic substrate after femtosecond laser treatment is not less than 8 μm; The surface roughness of the polymer material substrate after femtosecond laser treatment is no less than 20 μm.
7. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: In step S3, the plasma spraying gun power is 40-50 kW, the powder feeding amount is 15-25 g / min, and the spraying distance is 150-250 mm.
8. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: In step S3, when the biological coating is a titanium coating, the plasma spraying is performed under vacuum; When the biological coating is a hydroxyapatite coating, the plasma spraying is performed in an atmospheric environment.
9. The method for surface treatment of orthopedic implants based on femtosecond laser according to claim 1, characterized in that: In step S3, when the biological coating is a titanium coating, the thickness of the coating is 150-600 μm; When the biological coating is a hydroxyapatite coating, the thickness of the coating is 20-100 μm.
10. A surface modified orthopedic implant obtained by the surface treatment method according to any one of claims 1 to 9, characterized in that: The surface modified orthopedic implant is composed of an orthopedic implant substrate and a biological coating attached to the surface of the orthopedic implant substrate; When the biological coating is a titanium coating, the bonding force between the biological coating and the orthopedic implant substrate is not less than 25 MPa; when the biological coating is a hydroxyapatite coating, the bonding force between the biological coating and the orthopedic implant substrate is not less than 50 MPa.
Citation Information
Patent Citations
Orthopedic implant multilayer active coating and preparation method thereof
CN114099777A
High-entropy alloy coating for improving mechanical property and biocompatibility of titanium alloy and preparation method of high-entropy alloy coating
CN118109773A
Application of femtosecond laser in titanium or titanium alloy implantation material surface treatment
CN101264550A
Method for preparing hydroxylapatite coating by microplasma spraying
CN101591759A
Femtosecond laser preparation method of biomedical titanium and titanium alloy antibacterial activated surface periodic structure
CN114393312A
Cited By
Surface modified polyether-ether-ketone material as well as preparation method and application thereof
CN122255541A